Study of the Occurrence of Extreme Precipitation and Droughts in Northern Africa: Estimation of Return Periods and Return Levels - (:unkn) unknown (My University, 2020)
The occurrence of extreme hydro-climatic events such as floods and severe droughts has adverse impacts on society and economy of African countries, especially those of south of the Sahara, because of their low levels of development, which is associated with the high vulnerability of their populations. A study that analyzes their occurrence and their evolution, for the forecasting purposes, is a necessity for the region. This thesis focuses on the occurrence of the July–September (JAS) extreme rainfall and droughts in the northern Africa. Specifically, it addresses the issue of modeling their occurrences, estimating their return periods (RP) and their return levels (RL) in the context of stationary and non-stationary climate, and to evaluate the influence of the large-scale modes of climate variability (L-SMCV) on both their occurrence and the intensity of their RL. To conduct this investigation, we used monthly rainfall data from the Climatic Research Unit of the University of East Anglia in England, over the period 1901–2014; and those of four climate indices—the El Niño southern oscillation, the North Atlantic oscillation, the Pacific decadal oscillation, and the Atlantic multi-decadal oscillation—from the Global Climate Observing System Working Group on Surface Pressure. Two classical statistical approaches derived from the extreme value theory were used to identify and model the JAS extreme hydro-climatic events in the northern Africa: the peaks-over-threshold approach, which models the excesses above the threshold according to a generalized Pareto distribution, and the block maxima approach, which supposes that the maxima follow a distribution of generalized extreme value. The results reveal a good fit between these statistical approaches and the JAS extremes—wet and dry extremes—across the northern Africa. It appears that the areas with high occurrences of JAS extreme rainfall for a fixed RP are those of Guinean coastal regions and t
Keywords: African Research